Chronic pain management using combination of non-pharmacological therapy on elderly with arthritis rheumatoid: Case study - Devi, Hilda Mazarina; Setyowati, Lilis (Universitas Muhammadiyah Lamongan, 2023)
Arthritis rheumatoid are among the chronic conditions causing motor system decline in the elderly. The limited implementation of a non-pharmacological therapy combination involving warm compresses with deep breathing relaxation serves as the basis for this study. The aim of this scientific work is to conduct an analysis of pain management in elderly individuals with Arthritis rheumatoid.Method: A case study design was employed involving three clients, elderly individuals suffering from Arthritis rheumatoid. The nursing problem addressed was chronic pain (D.0078). The intervention applied to address chronic pain in these elderly individuals with an autoimmune condition involved a combination of warm compresses and deep breathing relaxation given three times over three consecutive days. The analysis was performed using the SMART (specific, measurable, achievable, relevant, and time-bound goals) method. The UNITRI FIKes gerontic nursing care format was used from data collection through action evaluation.Results: The case study revealed that on the initial assessment, all three elderly individuals experienced chronic pain at a moderate level. The planned nursing intervention was pain management, with pain level as the outcome criterion. After a three-day implementation, the issue of chronic pain was resolved in these elderly individuals, showing an increased ability to complete activities, reduced pain and grimacing, less protective attitude, and decreased sleep complaints.Conclusion: The combination therapy effectively reduced pain levels. This research serves as an addition to information and a resource for further studies concerning chronic pain management in elderly individuals with Arthritis rheumatoidKeywords: Arthritis, Breathing Exercises, Chronic pain, Hot Temperature, Rheumatoid